Worldview revolutions of the XIX–early XX centuries and image of Siberia in social and cultural practice of artists of Western Siberia in 1920’s–1930’s - Zh. E. Levina (Омский научный вестник: Серия "Общество. История. Современность")
In the era of the «visual revolution», the relevance of research on the artistic display of Siberia is due to the necessity to get a better understanding of how to create an image of the region, to analyze the peculiarities of reflection of the Siberian culture of the Soviet period, as well as to assess the interaction of European, Russian/Soviet and Siberian culture on a worldview level. The present article considers the problem of the representation of Siberia in the practice of West Siberian artists that has been little studied in Russian history. The degree of influence on the local authors’ work of the anthropological revolution of the XIX century and the Soviet cultural revolution is analyzed. The professional art associations of Siberia are shown as the ones which sensitively respond to domestic and Western European intellectual fashion trends and hobbies but at the same time being aware of their specificity of the community. The dynamics of artistic display about the natural, ethnic, social and cultural, everyday features of the West Siberian region is reflected in the article. The creation of an encyclopedic image of Siberia being free from local stereotypes and auto-stereotypes, in conditions of unification of themes and plots of the era of the Soviet cultural revolution is demonstrated